The Influence of Religiosity, Physical Evidence, Digital Marketing, And Islamic Lifestyle on Muslim Consumers’ Purchasing Decisions at an Nisaa’ Boutique Kudus - Muhammad Najib; Nurani Puspa Ningrum; Yunus Mustaqim (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the influence of religiosity, physical evidence, digital marketing, and Islamic lifestyle on the purchasing decisions of Muslim consumers at An Nisaa’ Boutique in Kudus. The results indicate that religiosity has a positive and significant effect on Muslim consumers’ purchasing decisions, as indicated by the t-value of 2.680 which is greater than the t-table value of 1.655. Physical evidence also has a positive and significant effect on purchasing decisions, as indicated by a t-value of 2.903 which is greater than the t-table value of 1.655. Furthermore, digital marketing significantly influences Muslim consumers’ purchasing decisions with a t-value of 16.595 which exceeds the t-table value of 1.655. Similarly, Islamic lifestyle has a positive and significant influence on purchasing decisions, with a t-value of 3.138 which is greater than the t-table value of 1.655. Simultaneously, religiosity, physical evidence, digital marketing, and Islamic lifestyle significantly influence Muslim consumers’ purchasing decisions, as indicated by the F-value of 90.150 which is greater than the F-table value of 3.91.